The craft of a Chinese commentator : Wang Bi on the Laozi - Wagner, Rudolf G. (SUNY series in Chinese philosophy and culture., 2000)
Wagner (Chinese studies, U. of Heidelberg, Germany) introduces a reading of the Laozi which differs greatly from the many translations currently available in the West, based on the work of Wang Bi (226-249), who dashed off a commentary on the Laozi and another on the Book of Changes -- two of the most enduring works of Chinese philosophy -- before his death at age 23. Wagner explores Wang Bi's craft as a scholarly commentator and as a philosopher in his own right, situating his work in the context of other competing commentaries.